Nanoparticle brain delivery: a guide to verification methods - Yokel, Robert A (Nanomedicine (London, England), 2020)
Many reports conclude nanoparticle (NP) brain entry based on bulk brain analysis. Bulk brain includes blood, cerebrospinal fluid and blood vessels within the brain contributing to the blood–brain and blood–cerebrospinal fluid barriers. Considering the brain as neurons, glia and their extracellular space (brain parenchyma), most studies did not show brain parenchymal NP entry. Blood–brain and blood–cerebrospinal fluid barriers anatomy and function are reviewed. Methods demonstrating brain parenchymal NP entry are presented. Results demonstrating bulk brain versus brain parenchymal entry are classified. Studies are reviewed, critiqued and classified to illustrate results demonstrating bulk brain versus parenchymal entry. Brain, blood and peripheral organ NP timecourses are compared and related to brain parenchymal entry evidence suggesting brain NP timecourse informs about brain parenchymal entry.